Integrasi Budaya Lokal dan Pendidikan Islam: Internalisasi Nilai Moral dalam Geguritan ”Nurani Peduli” pada Siswa Madrasah Ibtidaiyah - Ali Imron; Ari Saidul Mujazin (Bulletin of Indonesian Islamic Studies, 2022)
Moral education plays an important role in forming superior human beings. This paper aims to describe the moral values ​​contained in poetry or Geguritan "Nurani Peduli" by Handoyo Wibowo and look at the process of internalizing these moral values ​​in students of the Baitul Huda Islamic elementary school Semarang city through the Javanese language course. In addition, this paper also aims to see the implications of internalizing these moral values ​​for students. This paper uses a qualitative-phenomenological type of research that uses students, teachers, and school principals as research subjects. Based on the results of the study it was concluded that: First, the moral values ​​contained in geguritan include harmony, wisdom, humility, awareness, and development of taste. Second, the internalization process is carried out in three stages, namely the information stage by providing material on the moral values ​​contained in Geguritan "Nurani Peduli", the appreciation stage through direction and guidance and exemplary students, and the value application stage by providing motivation and encouragement to students to apply good grades in the form of actions. Third, the implications of internalization can be seen from three aspects, namely cognitive, affective, and psychomotor. Characterized by the integration of learning materials with an attitude of empathy, awareness, tolerance, and a sense of responsibility in social life.